2015
DOI: 10.1038/srep10831
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Two Heterozygous Mutations in Codon 723 of SLC26A4 on Deafness Phenotype Based on Molecular Dynamics Simulations

Abstract: A Chinese family was identified with clinical features of enlarged vestibular aqueduct syndrome (EVAS). The mutational analysis showed that the proband (III-2) had EVAS with bilateral sensorineural hearing loss and carried a rare compound heterozygous mutation of SLC26A4 (IVS7-2A>G, c.2167C>G), which was inherited from the same mutant alleles of IVS7-2A>G heterozygous father and c.2167C>G heterozygous mother. Compared with another confirmed pathogenic biallelic mutation in SLC26A4 (IVS7-2A>G, c.2168A>G), these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…It has been reported that the mutant pendrin comprised p.H723R is localized predominantly in endoplasmic reticulum and was found to lack the activity of anion exchange (18). It was also found that patients with two bi-allelic mutations of p.H723R or a compound heterozygous mutation with the other mutation often suffered from bilateral SHL (19)(20)(21). The other mutant allele c.1644_1645insA mutation of SLC26A4 was identified as a novel compound heterozygous mutation with p.H723R in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…It has been reported that the mutant pendrin comprised p.H723R is localized predominantly in endoplasmic reticulum and was found to lack the activity of anion exchange (18). It was also found that patients with two bi-allelic mutations of p.H723R or a compound heterozygous mutation with the other mutation often suffered from bilateral SHL (19)(20)(21). The other mutant allele c.1644_1645insA mutation of SLC26A4 was identified as a novel compound heterozygous mutation with p.H723R in the present study.…”
Section: Discussionsupporting
confidence: 68%
“…Several studies have investigated the genotype–phenotype correlation of deafness with SLC26A4 mutations. 35 40 Tsukamoto et al 26 reported that 78.13% (25/32) of EVA-positive patients carried SLC26A4 mutations in the Japanese population, while 46.94% (23/49) of such patients carried mutations in the Chinese population. 11 Additionally, we found that the overall mutations in the SLC26A4 gene accounted for 73.64% (648/880) of the patients with EVA.…”
Section: Discussionmentioning
confidence: 99%